Discomfort levels in four working postures in use during gari frying - Samuel, T.M.; Igbeka, J.C.; Kolawole, P. (2012)
Working postures adopted at work depend on the discomfort experienced as workers tend to opt for the most comfortable posture to them depending on the work at hand. The same is true for gari fryers. Four common working postures of gari-frying workers in Southwestern Nigeria are sitting beside (SB), sitting in front (SF), alternating sitting and standing (ASS) and standing (S). Discomfort levels in the identified postures were measured in 120 workers using Cornell Musculoskeletal Discomfort Questionnaire. Results of analyses indicated higher work-related musculoskeletal disorders (WMSDs) in the low back and upper back, placing musculoskeletal discomfort in the trunk. Specifically, WMSDs occurred in the hip-buttock, knee and neck for SB, hip-buttock for SF, low leg and shoulder for S and right forearm for ASS. This implies that ASS had the least discomfort among other postures analyzed. Therefore, ASS is recommended with seat modification to incorporate short backrest for reducing spinal loading.